ASSESSMENT OF THE GLOBAL BANKING SYSTEM FINANCIAL STABILITY - Igor Yushko (Izdevnieciba "Baltija Publishing", 2016)
Theoretical analysis of the global banking system concept is made. The principal factors of its financial stability are marked. Closeness and direction of relation are determined, and the quantitative estimate of principal relative indices of the global banking system financial stability is made. The comparative analysis of relative indices of the global banking system financial stability for years 2007 and 2015 permitted to mark principal factors and the key factor for both years, being the return on assets. Increase in the value of this factor evidences the growth of banking management role after the world financial crisis. In view of Basel III tightened requirements with respect to assets management, it is the profit use of bank's assets that guarantees banking services profits.